2021
DOI: 10.3389/fsurg.2021.655755
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Emergent Groin Hernia Repair—An Analysis From the Herniamed Registry

Abstract: Introduction: While the proportion of emergency groin hernia repairs in developed countries is 2.5–7.7%, the percentage in developing countries can be as high as 76.9%. The mortality rate for emergency groin hernia repair in developed countries is 1.7–7.0% and can rise to 6–25% if bowel resection is needed. In this present analysis of data from the Herniamed Registry, patients with emergency admission and operation within 24 h are analyzed.Methods: Between 2010 and 2019 a total of 13,028 patients with emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Older patients are unique in multiple ways, and therefore, physicians approach them differently [4]. IH is a common disease in older individuals, and its repair is associated with low morbidity and mortality rates; however, these patients are occasionally offered watchful waiting [1,4,[6][7][8]. Our study demonstrated that older patients undergoing IH repair have comparable results to those of younger patients with no significant perioperative risk or complications.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Older patients are unique in multiple ways, and therefore, physicians approach them differently [4]. IH is a common disease in older individuals, and its repair is associated with low morbidity and mortality rates; however, these patients are occasionally offered watchful waiting [1,4,[6][7][8]. Our study demonstrated that older patients undergoing IH repair have comparable results to those of younger patients with no significant perioperative risk or complications.…”
Section: Discussionmentioning
confidence: 59%
“…Having a higher BMI could explain this association; as in female patients, the rate of obesity (BMI ≥30) was 38% versus 24% in male patients. Köckerling et al [7] reported a similar correlation for older women who underwent emergency groin surgery. They found that patients who required bowel resection during emergency groin hernia repair and female patients who were ≥66 years had unfavorable perioperative outcomes [7].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations